A case of Invasive pulmonary infection caused by novel species of Perenniporia. Issue 11 (15th July 2014) - Detporntewan, Pitaks; Chindamporn, Ariya; Worasilchai, Navaporn; Suankratay, Chusana
Summary Perenniporia species, members of basidiomycetes, are known as decay fungi from wood of hardwood tree species. The clinical significance of these non‐sporulating fungi from respiratory tract specimens is unknown. They have frequently been discarded as contaminants. There was only one case report of pulmonary fungal ball with positive culture for a Perenniporia species. We report herein a case of invasive pulmonary infection caused by the novel species of Perenniporia in a 44‐year‐old woman with active systemic lupus erythematosus who was successfully treated with voriconazole.